Controlled Low-Strength Material Using Industrial Waste Incineration Bottom Ash and Refined Kaolin - Razak, H.A.; Naganathan, S.; Hamid, S.N.A. (2010)
This paper reports the details of investigations carried out to study the performance of industrial waste incineration bottom ash and refined kaolin to produce controlled low-strength material (CLSM). CLSM mixes were designed with varying amounts of incineration bottom ash, refined kaolin, and cement. Water content was adjusted to get sufficient flowability. Tests for density, stiffening time, bleed, settlement, sorptivity, water absorption, moisture content, California bearing ratio, initial surface absorption, and compressive strength were carried out on the CLSM mixtures. Study for corrosivity and leaching of heavy metals and salts on the bleed and leachate were also performed. The compressive strength of CLSM tested ranged from 0.36 to 4.40 MPa. CBR values ranged from 10 to 46 and ISAT values at 1 hour from 0.56 to 4.76 ml/m2/s. None of the heavy metals tested exceeded the threshold limits in leachate. Addition of kaolin controls the compressive strength development, and reduces initial surface absorption, California bearing ratio, and water absorption values. It is shown that the incineration bottom ash, along with refined kaolin, can be successfully employed in CLSM, thereby contributing to sustainability in civil engineering practice.